Does the flutter kick increase hand propulsion in front crawl swimming? - Homoto, K.; Gonjo, T.; Takagi, H.; Kudo, S.; Sengoku, Y.; Tsunokawa, T.; Koga, D.; Homma, M. (Sports Biomechanics, 2024)
This study aimed to investigate the effect of the flutter kick on the propulsive force generated by a stroke. Eight male swimmers performed 20 m front crawl trials under two conditions: the Whole Condition, involving maximum effort (T100%) and stroke frequencies at 70, 80, and 90% of T100%, and the Arm Condition, which excluded the flutter kick and matched stroke frequencies with the Whole Condition. Various parameters, including swimming velocity, stroke frequency, stroke length, three-dimensional (3D) resultant hand speed, and hand propulsion were calculated based on underwater 3D motion analysis and hand pressure distribution measurements. A two-way repeated-measures ANOVA was conducted to assess differences, considering the conditions and instructed frequencies as the two factors. There was no significant interaction between the condition and intensity for any of the variables. There was a significant main effect of condition on swimming velocity and stroke length, with these variables being 16.9-18.5% higher and 17.3-19.5% longer, respectively, in the Whole Condition compared to the Arm Condition. However, there was no difference in hand propulsion between the conditions, and it was clarified that the flutter kick did not affect hand propulsion at any swimming velocity.